1996 international trade statistics yearbook = 1996 annuaire statistique du commerce international. (International Financial Statistics ;, 1997)
he International Financial Statistics Yearbook, usually published in September, contains available annual data covering 12 years for countries appearing in the monthly issues of IFS. The IFS service is the standard source of international financial statistics. Additional time series in country tables and some additional tables of area and world aggregates are included in the Yearbook.